The Ripple Effects of Financial Fraud: Investor Trust and Risk Appetite Post-Kangmei Pharmaceutical - Sun , Hao (Transactions on Economics, Business and Management Research, 2024)
The financial fraud at Kangmei Pharmaceutical (stock code: 600518) has had profound implications for retail investors. This paper, through data analysis, explores the correlation between information asymmetry and investment outcomes for retail investors. Information asymmetry often leaves retail investors unable to access the true financial state and operational conditions of companies, leading them to make speculative investments. Post-exposure, as information transparency increased, retail investors became aware of the company's financial issues and rushed to sell, causing a stock plunge. This highlights how information asymmetry not only affects investment decisions but also amplifies market volatility. To mitigate risks from information asymmetry, regulators must strengthen oversight and penalties, improve disclosure transparency and authenticity, while investors need to enhance self-protection awareness and information gathering and analysis capabilities. Only then can we minimize the impact of information asymmetry on retail investors and uphold fairness and stability in financial markets. This paper suggests that by implementing a robust regulatory framework and encouraging proactive investor education, we can better safeguard retail investors from the detrimental effects of information asymmetry, thereby fostering a more resilient and equitable financial market ecosystem.